2022
DOI: 10.1002/aqc.3780
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for multiple refugia and hotspots of genetic diversity for Westralunio carteri, a threatened freshwater mussel in south‐western Australia

Abstract: Intraspecific genetic diversity provides the evolutionary potential to adapt to changing environments and ‘hotspots’ of high intraspecific diversity are recognized as key targets for conservation. In south‐western Australia, intraspecific genetic diversity for mesic taxa is not uniformly distributed. Many species comprise highly divergent lineages with unique haplotypes resulting from contraction to refugia during historical arid cycles. Sampling strategies in studies of the region’s unique and ancient freshwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 94 publications
(177 reference statements)
0
28
0
Order By: Relevance
“…the Chindwin and the upper Ayeyarwady). Moreover, the two basins may represent hidden ‘hotspots’ of high intraspecific diversity for widespread species, as shown recently for Westralunio carteri Iredale, 1934 in Australia (Benson et al, 2022).…”
Section: Discussionmentioning
confidence: 79%
“…the Chindwin and the upper Ayeyarwady). Moreover, the two basins may represent hidden ‘hotspots’ of high intraspecific diversity for widespread species, as shown recently for Westralunio carteri Iredale, 1934 in Australia (Benson et al, 2022).…”
Section: Discussionmentioning
confidence: 79%
“…Two recent studies have investigated phylogeographic structuring and the existence of Evolutionary Significant Units (ESUs) and Molecular Operational Taxonomic Units’ (MOTUs) in W. carteri 27 , 28 . Klunzinger et al 27 applied four species delimitation models based on 46 COI mtDNA sequences spanning 13 populations of W. carteri, which revealed unanimous support for at least two MOTUs: “ W. carteri ” I from west coast drainages and “ W. carteri ” II + III from drainages of the south coast lower southwest of southwestern Australia.…”
Section: Introductionmentioning
confidence: 99%
“…The authors recommended further research was required to better characterise the observed differentiation among lineages and their distribution. Subsequent work by Benson et al 28 incorporated COI and 16S sequences from an additional 119 individuals from 19 populations previously unsampled and showed that the distribution of the two primary lineages rarely overlapped, and that the third lineage appeared to be restricted to just two river systems.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has identified the occurrence of two distinct, geographically separated lineages (and putative new species) within the range of the currently described W. carteri (Klunzinger et al, 2021;Benson et al, 2022). This study was conducted in the range of the lineage "W. carteri" I of Klunzinger et al (2021), which is found on the west coast of south-western Australia.…”
Section: Study Areamentioning
confidence: 99%
“…Westralunio carteri Iredale, 1934 (Hyriidae) is endemic to south-western Australia. It is the only freshwater mussel species currently described from the region, although recent molecular studies have identified distinct, spatially structured genetic lineages and highlighted the need for a taxonomic revision (Klunzinger et al, 2021;Benson et al, 2022). Westralunio carteri (sensu lato) is found only in the South-west Coast Drainage Division of Western Australia, being largely restricted to lotic and lentic systems in forested areas within 100 km of the coast (Klunzinger et al, 2015).…”
Section: Introductionmentioning
confidence: 99%